4D marine conservation networks: Combining 3D prioritization of present and future biodiversity with climatic refugia. (5th June 2022) - Doxa, Aggeliki; Almpanidou, Vasiliki; Katsanevakis, Stelios; Queirós, Ana M.; Kaschner, Kristin; Garilao, Cristina; Kesner‐Reyes, Kathleen; Mazaris, Antonios D.
Abstract: Given the accelerating rate of biodiversity loss, the need to prioritize marine areas for protection represents a major conservation challenge. The three‐dimensionality of marine life and ecosystems is an inherent element of complexity for setting spatial conservation plans. Yet, the confidence of any recommendation largely depends on shifting climate, which triggers a global redistribution of biodiversity, suggesting the inclusion of time as a fourth dimension. Here, we developed a depth‐specific prioritization analysis to inform the design of protected areas, further including metrics of climate‐driven changes in the ocean. Climate change was captured in this analysis by considering the projected future distribution of >2000 benthic and pelagic species inhabiting the Mediterranean Sea, combined with climatic stability and heterogeneity metrics of the seascape. We identified important areas based on both biological and climatic criteria, where conservation focus should be given in priority when designing a three‐dimensional, climate‐smart protected area network. We detected spatially concise, conservation priority areas, distributed around the basin, that protected marine areas almost equally across all depth zones. Our approach highlights the importance of deep sea zones as priority areas to meet conservation targets for future marine biodiversity, while suggesting that spatial prioritization schemes, that focus on a static two‐dimensional distribution of biodiversity data, might fail to englobe both the vertical properties of species distributions and the fine and larger‐scale impacts associated with climate change. Abstract : Incorporating the potential future impacts of climate change and the three‐dimensionality of marine life in spatial conservation planning is challenging but urgently needed. Here, we develop a 4D prioritization framework, based on the depth‐specific (3D) current and future distributions of >2000 benthic and pelagic species, inhabiting the Mediterranean Sea, in combination with sea surface and bottom thermal data for present and future climates. We identify vertically coherent, conservation priority areas, mostly situated in the western Mediterranean, while we stress the importance of deep sea zones as priority areas, to meet conservation targets for future marine biodiversity.